2019
DOI: 10.1590/1676-0611-bn-2019-0746
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Biomphalaria spp. freshwater snails and associated mollusks in areas with schistosomiasis risk, using molecular and spatial analysis tools

Abstract: The Middle Paranapanema River region of São Paulo, Brazil is home to significant diversity of Biomphalaria species and is very vulnerable to health and environmental impacts such as schistosomiasis. This study updates freshwater malacological surveys for ecosystems in one portion of the Middle Paranapanema River Basin, with emphasis on the genus Biomphalaria. Snails were collected from 114 distinct bodies of water between 2015 and 2018. Biomphalaria specimens were identified according to morphological and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…The numbers (N°) in Figure 1 C correspond to the collection points presented in Table 1 . Source: IBGE 36 , 37 ; SMA 38 ; SUCEN/Palasio et al 14 ; SINAN/CVE. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The numbers (N°) in Figure 1 C correspond to the collection points presented in Table 1 . Source: IBGE 36 , 37 ; SMA 38 ; SUCEN/Palasio et al 14 ; SINAN/CVE. …”
Section: Methodsmentioning
confidence: 99%
“…The schistosomiasis cases observed in Ourinhos are probably associated with B. glabrata , which is a natural host to S. mansoni in the municipality 10 , 11 . This species was initially identified in Ourinhos in 1919 12 and continues to proliferate in water bodies in this municipality 13 , 14 . B. tenagophila and B. straminea, two other S. mansoni intermediate-host (IH) species, have also been described/observed in the area 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomphalaria straminea is the main intermediate host for S. mansoni in the northeast of Brazil (Figueiredo 1989, Ohlweiler et al 2010. Its high capacity to spread through new water collections (Pointier et al 2005, Palasio et al 2019) may facilitate the expansion of the species in the state of São Paulo. This poses a challenge to control the disease, which requires monitoring and constant mapping of water bodies and the snails associated with them.…”
Section: Morphological Taxonomy Integrated With Molecular Taxonomy Inmentioning
confidence: 99%
“…In Mecha North West Ethiopia, 46.1% Helix, 23.7% Lymnaea, 13.2% Bulinus, 9.2% Planorbin, and 7.9% Oncomelania (40) was reported. In Middle Paranapanema River region of São Paulo, Brazil, of the 10,722 snails collected, 86.7% were in the Planorbidae family (75.5% Biomphalaria and 11.2% Drepanotrema) and 13.3% were other non-Planorbidae species (Lymnaea, Melanoides, Physa and Pomacea)(41). This variation might be due to seasonality of snail abundance and freshwater snails are generally encountered in freshwater body that is polluted with human and animal excreta.On the other hand, this nding was in contrast when compared to studies carried out in Kisumu City, western Kenya, which reported out of 1,059 snails collected, 407 (38.4%) were putatively identi ed as B. sudanica,425(40.1%) as B. pfeifferi and 227(21.5%) as Bulinus globosus(42).…”
mentioning
confidence: 99%